2019
DOI: 10.1007/s11606-019-05086-4
|View full text |Cite
|
Sign up to set email alerts
|

VA/DoD Clinical Practice Guideline: Diagnosis and Treatment of Low Back Pain

Abstract: , the U.S. Department of Veterans Affairs (VA) and U.S. Department of Defense (DoD) approved the joint Clinical Practice Guideline (CPG) for Diagnosis and Management of Low Back Pain. This CPG was intended to provide healthcare providers a framework by which to evaluate, treat, and manage patients with low back pain (LBP). METHODS: The VA/DoD Evidence-Based Practice Work Group convened a joint VA/DoD guideline development effort that included a multidisciplinary panel of practicing clinician stakeholders and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(151 citation statements)
references
References 33 publications
(43 reference statements)
1
129
0
5
Order By: Relevance
“… 20 27 29 30 37 38 41 42 46 CPGs reported that women tend to have a higher prevalence of LBP and are more likely to seek care for LBP 20 27 37 42 One pregnancy-specific reference was made within Category 3, stating that two-thirds of pregnant women experience LBP. 38 Category 3 was the only category that referenced male sex or gender, stating that men, more often than women, experience LBP as a result of manual material handling. 41 Men also have a higher risk of developing ankylosing spondylitis and spondylolysis.…”
Section: Resultsmentioning
confidence: 99%
“… 20 27 29 30 37 38 41 42 46 CPGs reported that women tend to have a higher prevalence of LBP and are more likely to seek care for LBP 20 27 37 42 One pregnancy-specific reference was made within Category 3, stating that two-thirds of pregnant women experience LBP. 38 Category 3 was the only category that referenced male sex or gender, stating that men, more often than women, experience LBP as a result of manual material handling. 41 Men also have a higher risk of developing ankylosing spondylitis and spondylolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one CPGs met the inclusion and exclusion criteria, of which seven (33.3%) were devoted to neck pain [28,[30][31][32][33][34]49] (i.e., Canada, KNGF, APTA, DHA, OPTIMa, Scottish and SIMFER CPGs), fourteen (66.6%) CPGs were devoted to back pain [33,[35][36][37][38][39][40][41][42][43][44][45][46][47] (i.e., ACP, ACI, Belgium, Canada, DHA, German, Globe et al, NDMG, KNGF, Scottish, Colorado, TOP, VA/DoD and NICE CPGs), and 3 (14.3%) CPGs were devoted to sciatica [38,47,48] (i.e., DHA, NASS and NICE CPGs). Some guidelines contained more than one site.…”
Section: Resultsmentioning
confidence: 99%
“…[33] In addition, some guidelines suggested that manual therapy could be applied if self-care and medication therapy did not provide signi cant improvements [36] or that it could be offered as a part of multimodal management. [37,39,46,47] One CPG recommended massage for treating acute and subacute low back pain, [35] while two guidelines indicated that massage was not recommended for acute low back pain but could be considered for chronic low back pain. [40,41] One guideline stated that there was insu cient evidence to show the effect of manual therapy including massage.…”
Section: Manual Therapymentioning
confidence: 99%
“…We will include studies on patients that have been diagnosed as LMS by clinicians based on Evidence-Based Clinical Guidelines for Multidisciplinary Spine Care: Diagnosis & Treatment of Low Back Pain, [ 12 ] VA/DoD Clinical Practice Guideline: Diagnosis and Treatment of Low Back Pain and Criteria for Diagnosis, [ 13 ] and Efficacy of TCM Diseases. [ 14 ] There will be no restriction on age, gender, ethnicity, and profession.…”
Section: Methodsmentioning
confidence: 99%